A graphene-enhanced benzoxazine resin composite material and its preparation method and application

By adding an appropriate amount of graphene to the benzoxazine resin composite material and using the heating curing method, composite materials with excellent mechanical, thermal and electrical conductivity were prepared, which solved the problem of poor mechanical properties of existing materials and was suitable for large-scale production.

CN119350800BActive Publication Date: 2025-04-25CHANGZHOU HONGJU ELECTRIC TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411946133.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-25
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

The existing benzoxazine resin composite materials have poor mechanical properties and are difficult to produce on a large scale, which cannot meet the practical application needs.

Method used

By grinding the benzoxazine resin monomer into powder and mixing it with graphene, the graphene-reinforced benzoxazine resin composite material is prepared by heating curing method, and the mass of graphene accounts for 8-15% of the mass of the benzoxazine resin monomer.

Benefits of technology

The prepared composite materials have excellent mechanical properties, thermal conductivity and electrical conductivity, which solves the problem of poor mechanical properties of existing materials and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350800B_ABST
    Figure CN119350800B_ABST
Patent Text Reader

Abstract

The invention discloses a graphene-enhanced benzoxazine resin composite material and its preparation method and application, the composite material is formed by grinding a benzoxazine resin monomer into powder and curing with graphene at a high temperature, the mass of the graphene is 8-15% of the mass of the benzoxazine resin monomer, the particle size of the benzoxazine monomer powder is 10-700 μm, and the benzoxazine monomer is a bifunctional benzoxazine monomer. In the material prepared by the present invention, a layer of dense graphene is coated on the surface of benzoxazine, and then cured at a high temperature, and graphene will form multiple heat conduction paths inside the composite material, thereby constructing an internal heat conduction network. The composite material of the present invention not only retains the high heat resistance, flame retardancy, near-zero volume shrinkage, and moisture resistance of benzoxazine, but also has excellent thermal conductivity and mechanical properties, and has more excellent performance than the benzoxazine / graphene composite material prepared by traditional melt blending.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to a benzoxazine resin composite material, and specifically relates to a graphene-reinforced benzoxazine resin composite material and a preparation method and application thereof. Background Art

[0002] Graphene is a two-dimensional network of carbon atoms with a honeycomb structure and excellent thermal, mechanical and electrical properties. 2 Orbital hybridization provides graphene with extremely high phonon group velocities and a simple lattice. Defect-free single-layer graphene exhibits an in-plane thermal conductivity of 3000-5000 W / mK at room temperature, making it one of the best known thermal conductive materials. In addition, the conductivity of graphene can reach 6000 S / cm, exceeding that of carbon-based fillers such as copper. These excellent properties have attracted many scientists to use it as a filler in different polymers to improve the electrical, conductive and mechanical properties of polymer matrices, which usually have thermal insulation and insulating properties.

[0003] As a new type of thermosetting resin, benzoxazine resin is developed on the basis of traditional phenolic resin. It not only retains the advantages of traditional phenolic resin, but also overcomes its disadvantages. However, benzoxazine resin also has some disadvantages: the viscosity of benzoxazine resin is relatively small, which is difficult to meet the existing process requirements; the thermal curing temperature is high, the curing time is long, and like many thermosetting resins, there is a problem of large brittleness of the cured product. Therefore, inorganic micro-nanoparticles are often used to improve its toughness and thermal conductivity. In practical applications, adding fillers by direct melt blending often requires a very high filling ratio to achieve a gain effect. The above-mentioned inorganic fillers include but are not limited to ceramic fillers alumina aluminum carbide, carbon-based fillers graphene, carbon nanotubes, etc. The chemical modification method has complex process operations, time-consuming and energy-consuming. Therefore, the use of simple processes and efficient preparation of benzoxazine composite materials is of great significance to the promotion of the application of benzoxazine resins. Summary of the invention

[0004] Purpose of the invention: In view of the problems existing in the prior art, the present invention provides a graphene-reinforced benzoxazine resin composite material. The graphene-reinforced benzoxazine resin composite material prepared by the present invention has excellent mechanical properties, thermal conductivity and electrical conductivity, and effectively solves the problem that the current benzoxazine composite material has poor mechanical properties and cannot be mass-produced.

[0005] The present invention also provides a preparation method and application of the graphene-reinforced benzoxazine resin composite material.

[0006] Technical solution: In order to achieve the above-mentioned purpose, the graphene-reinforced benzoxazine resin composite material of the present invention is formed by grinding a benzoxazine resin monomer into powder and curing it with graphene at a high temperature, wherein the mass of the graphene is 8-15% of the mass of the benzoxazine resin monomer; the particle size of the benzoxazine monomer powder is 10-700 μm, and the benzoxazine monomer is a bifunctional benzoxazine monomer, and its structure is shown in any one of the following:

[0007] ,

[0008] ,

[0009] ,

[0010] .

[0011] Wherein, the particle size of the benzoxazine monomer powder is between 10 μm and 700 μm.

[0012] Preferably, the benzoxazine monomer powder has a particle size of 50 μm to 400 μm.

[0013] Preferably, the benzoxazine monomer has a symmetrical structure, a high degree of conjugation, a high molecular weight, and a certain viscosity.

[0014] Wherein, the graphene is few-layer graphene.

[0015] The method for preparing the graphene-enhanced benzoxazine resin composite material of the present invention comprises the following steps:

[0016] (1) Grinding benzoxazine resin monomer into powder;

[0017] (2) mixing benzoxazine resin monomer powder and graphene;

[0018] (3) The mixed composite material powder is heated and solidified to obtain a composite material.

[0019] Wherein, the mass of the graphene in step (2) is 8-15% of the mass of the benzoxazine resin monomer.

[0020] Preferably, the mass of the graphene in step (2) is 10-12% of the mass of the benzoxazine resin monomer.

[0021] Preferably, the mass of the graphene in step (2) is 10% of the mass of the benzoxazine resin monomer.

[0022] Wherein, the stirring speed in step (2) is 700-2500 rpm, and the stirring time is 10 min-2 h.

[0023] The specific heating process of the heating and curing in step (3) is as follows: heating to 140-150°C and keeping warm for 1-2h, 160-170°C and keeping warm for 1-2h, 180-190°C and keeping warm for 1-2h, 200-210°C and keeping warm for 1-2h, and 220-230°C and keeping warm for 1-2h.

[0024] Preferably, in step (3), the mixed composite material is filled into a mold and heated to cure. The shape of the curing mold can be round, square or any other required shape, and the mold material can be steel or polytetrafluoroethylene.

[0025] Preferably, the heating process is as follows: sequentially heating to 140°C for 1 hour, 160°C for 1 hour, 180°C for 1 hour, 200°C for 1 hour, and 220°C for 1 hour.

[0026] Application of the graphene-enhanced benzoxazine resin composite material of the present invention in electronic components and battery heat dissipation materials.

[0027] The preparation method of the present invention comprises the steps of grinding a resin monomer into powder, preparing a graphene-coated resin monomer powder, preparing a benzoxazine / graphene composite material, and the like. In the benzoxazine / graphene composite material system prepared by the present invention, benzoxazine is coated with a layer of graphene on the surface by its own viscosity, and then the adsorption effect is enhanced by conjugation. When the benzoxazine powder coated with a layer of graphene is open-ring cured, the graphene layers coated on the surface are connected to each other, and a graphene heat-conducting network path is constructed inside the material, giving the material excellent thermal conductivity and electrical conductivity. At the same time, the mechanical properties of the material are improved. The preparation process of the present invention is simple, the equipment requirements are low, and it is suitable for large-scale production. The prepared composite material is not limited by the shape of the mold, and has a wide range of application scenarios in the field of heat dissipation.

[0028] The preparation method of the benzoxazine / graphene composite material of the present invention is obtained by powder blending benzoxazine monomer powder with a specific particle size and a specific ratio and graphene nanosheets without adding other additives. The present invention assembles through the viscosity of the resin itself and the conjugation effect between the powders, and can avoid the use of additives such as a disperser. The present invention has a simple process and low cost, while a large amount of additives such as organic solvents are usually used in the assembly of composite materials and graphene, and are discarded after being assembled into composite materials, resulting in waste of resources.

[0029] The present invention utilizes the viscosity of the resin itself and the conjugation effect between the powders to coat tiny graphene nanosheets on the surface of the resin particles. After curing, the graphene coated on the surface of the resin particles can be connected to each other to form a three-dimensional heat conduction path inside the composite material, which is beneficial to the transfer of heat. The present invention combines the principle of building a three-dimensional space network to enhance thermal conductivity. The assembly process does not involve any organic additives, the preparation process is simple, the method is green and safe, and it can be mass-produced at low cost. At the same time, it solves the problem that the current existing production is mainly based on melting, and uses organic additives to achieve vacuum-assisted self-assembly, which is limited to being prepared into a thin film shape. The material prepared by the present invention can be prepared into any shape, such as strips and circles, through the corresponding mold.

[0030] Beneficial effects: Compared with the prior art, the present invention has the following advantages:

[0031] In the present invention, the graphene powder is adsorbed on the surface by the sticky benzoxazine monomer during the stirring process, and the adsorption effect is enhanced by the π-π effect, so that the surface of the benzoxazine is coated with a layer of dense graphene, and then the graphene forms multiple heat conduction paths inside the composite material during the temperature rise and curing, thereby constructing an internal heat conduction network. The composite material retains the high heat resistance, flame retardancy, near zero volume shrinkage, and moisture resistance of benzoxazine, and has excellent thermal conductivity and mechanical properties, and has better performance than the traditional benzoxazine / graphene composite material prepared by melt blending.

[0032] The present invention combines the characteristics of benzoxazine materials, such as high content of aromatic rings (high conjugation effect), slight viscosity, good heat resistance, and curing without auxiliary agents, with the construction of a three-dimensional thermal conductive network to effectively improve the thermal conductivity of the material, thereby achieving efficient assembly of the material and graphene. The process is simple, green and environmentally friendly, suitable for large-scale production, and the prepared composite material has significantly improved thermal conductivity, electrical conductivity and mechanical properties compared to benzoxazine resin. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 is a scanning electron microscope image of the cross section of the benzoxazine / graphene composite material obtained in Example 1;

[0034] Figure 2 is a scanning electron microscope image of the cross section of the polybenzoxazine obtained in Example 1;

[0035] Figure 3 This is a scanning electron microscope image of the graphene-coated benzoxazine monomer powder obtained in Example 1. DETAILED DESCRIPTION

[0036] The present invention can be better understood according to the following examples. However, it is easy for those skilled in the art to understand that the contents described in the examples are only used to illustrate the present invention, and should not and will not limit the present invention described in detail in the claims.

[0037] The experimental methods described in the examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.

[0038] Examples 1-3 used the thienylbenzoxazine resin monomer prepared in Example 1 of patent CN 117004179A. The peak polymerization temperature of the monomer was 203° C. and the structural formula was as follows:

[0039] .

[0040] The graphene powder is commercially available graphene powder prepared by atmospheric phase exfoliation method of Harbin Institute of Technology (thickness ≤ 4 nm, number of layers 1-10, particle size 6-10 μm, carbon content ≥ 99.9%). Specifically, the powder purchased is few-layer graphene powder.

[0041] Example 1

[0042] 1. First, the benzoxazine resin monomer and graphene are dried in a vacuum oven to remove moisture. Then, the benzoxazine resin monomer is ground into powder at room temperature, and a sieve is used to filter the powder to obtain a particle size of 50-400 μm.

[0043] 2. At room temperature, weigh 10% by mass of graphene and the ground and screened benzoxazine resin monomer powder, add them into a blender and stir for 1 h. Set the speed to 1500 rpm.

[0044] 3. Collect the composite material preform after stirring, add it into the curing mold, and finally heat it up to perform ring-opening polymerization to obtain the target product.

[0045] The specific heating process of the temperature-raising ring-opening copolymerization is as follows: heat to 140°C and keep warm for 1 hour, 160°C and keep warm for 1 hour, 180°C and keep warm for 1 hour, 200°C and keep warm for 1 hour, and 220°C and keep warm for 1 hour.

[0046] The composite material preform powder prepared in this embodiment (before curing and heating) has a morphology as follows: Figure 3 As shown in Figure 2, the interface of the composite material after curing is as follows: Figure 1 As shown, Figure 2 This is an electron microscope image of the cross section of pure benzoxazine resin after curing.

[0047] The composite material prepared in this embodiment has a thermal conductivity of 1.06 W / mK, an electrical conductivity of 1.12 S / cm, a tensile strength of 53.4 MPa, and a flexural strength of 126 MPa.

[0048] Example 2

[0049] 1. First, the benzoxazine resin monomer and graphene are dried in a vacuum oven to remove moisture. Then, the benzoxazine resin monomer is ground into powder at room temperature, and a sieve is used to filter the powder so that the particle size is 10-400 μm.

[0050] 2. At room temperature, weigh 10% mass fraction of graphene of benzoxazine resin monomer and the ground and screened benzoxazine resin monomer powder, add them into a blender and stir for 2 hours, and set the speed to 1500 rpm.

[0051] 3. Collect the composite material preform after stirring, add it into the curing mold, and finally heat it up to perform ring-opening polymerization to obtain the target product.

[0052] The specific heating process of the temperature-raising ring-opening copolymerization is as follows: heat to 140°C and keep warm for 1 hour, 160°C and keep warm for 1 hour, 180°C and keep warm for 1 hour, 200°C and keep warm for 1 hour, and 220°C and keep warm for 1 hour.

[0053] The composite material prepared in this embodiment has a thermal conductivity of 0.83 W / mK, an electrical conductivity of 1.08 S / cm, a tensile strength of 52.9 MPa, and a flexural strength of 119 MPa.

[0054] Example 3

[0055] 1. First, the benzoxazine resin monomer and graphene are dried in a vacuum oven to remove moisture. Then, the benzoxazine resin monomer is ground into powder at room temperature, and a sieve is used to filter the powder to obtain a particle size of 400-700 μm.

[0056] 2. At room temperature, weigh 10% mass fraction of graphene of benzoxazine resin monomer and the ground and screened benzoxazine resin monomer powder, add them into a blender and stir for 10 min, with the speed set to 2000 rpm.

[0057] 3. Collect the composite material preform after stirring, add it into the curing mold, and finally heat it up to perform ring-opening polymerization to obtain the target product.

[0058] The specific heating process of the temperature-raising ring-opening copolymerization is as follows: heat to 140°C and keep warm for 1 hour, 160°C and keep warm for 1 hour, 180°C and keep warm for 1 hour, 200°C and keep warm for 1 hour, and 220°C and keep warm for 1 hour.

[0059] The composite material prepared in this embodiment has a thermal conductivity of 0.93 W / mK, an electrical conductivity of 0.99 S / cm, a tensile strength of 52.1 MPa, and a flexural strength of 122 MPa.

[0060] Example 4

[0061] The furan-based benzoxazine resin monomer was prepared according to the preparation method of Example 1 in patent CN 117004179A, and its structure is:

[0062] ,

[0063] A composite material was prepared using furan-based benzoxazine resin monomers according to the method in Example 1, and had a thermal conductivity of 0.94 W / mK, an electrical conductivity of 1.03 S / cm, a tensile strength of 59.2 MPa, and a flexural strength of 116.7 MPa.

[0064] Example 5

[0065] Referring to the preparation method of Example 1 in patent CN 117004179A, a naphthalene-based benzoxazine resin monomer is prepared, and its structure is:

[0066] ,

[0067] A composite material was prepared using a naphthalene-based benzoxazine resin monomer according to the method in Example 1, and had a thermal conductivity of 1.12 W / mK, an electrical conductivity of 1.22 S / cm, a tensile strength of 44.7 MPa, and a flexural strength of 89.9 MPa.

[0068] Example 6

[0069] The benzene benzoxazine resin monomer was prepared according to the preparation method of Example 1 in patent CN 117004179A, and its structure is:

[0070] ,

[0071] The composite material was prepared by using a benzene benzoxazine resin monomer according to the method in Example 1, and had a thermal conductivity of 0.87 W / mK, an electrical conductivity of 0.91 S / cm, a tensile strength of 50.6 MPa, and a flexural strength of 108.6 MPa.

[0072] Comparative Example 1

[0073] Comparative Example 1 adopts the same preparation method as Example 1, except that in step 1: the particle size of the benzoxazine resin monomer powder is 1-10 μm. Since the resin particles are very small, the graphene in the prepared coated powder is difficult to be adsorbed on the surface of the resin monomer.

[0074] Comparative Example 2

[0075] Comparative Example 2 adopts the same preparation method as Example 1, with the only difference being that in step 1: when the particle size of the benzoxazine resin monomer powder is about 1000 μm, the prepared composite material has a thermal conductivity of 0.54 W / mK, which is significantly lower than the thermal conductivity of Example 1. This is mainly because the particle size is too large, making it difficult to completely coat, and the formed thermal conduction path will have many short circuits. Moreover, after solidification in a space of the same size, the thermal conduction path composed of graphene inside the material will also be reduced.

[0076] Comparative Example 3

[0077] Comparative Example 3 adopts the same preparation method as Example 1, except that in step 1: the benzoxazine resin monomer powder used is a monofunctional benzoxazine, and the structure is as follows:

[0078] .

[0079] The prepared composite material has a thermal conductivity of 0.58 W / mK, an electrical conductivity of 0.72 S / cm, a tensile strength of 32.1 MPa, and a flexural strength of 68 MPa. The resin monomer in this comparative example is a monofunctional structure, and its mechanical properties are significantly inferior to those of a bifunctional structure. The degree of conjugation of the monofunctional structure is also lower than that of the bifunctional structure, resulting in poor bonding with graphene. Its thermal conductivity and electrical conductivity effects are also significantly inferior to those in Example 1.

[0080] Comparative Example 4

[0081] Comparative Example 4 adopts the same preparation method as Example 1, with the only difference being that in step 2: 20% of the mass fraction of graphene in the resin monomer is weighed and stirred together. The thermal conductivity and electrical conductivity of the prepared composite material are almost unchanged, but the mechanical properties are significantly reduced compared with those in Example 1, with a tensile strength of 23.4 MPa and a flexural strength of 54 MPa.

[0082] At the same time, when the resin monomer with a mass fraction of 5% graphene is weighed and stirred together, the mechanical properties of the prepared composite material do not change significantly, but the thermal conductivity and electrical conductivity are significantly reduced compared with Example 1, with the thermal conductivity being 0.41 W / mK and the electrical conductivity being 0.53 S / cm.

[0083] Comparative Example 5

[0084] Comparative Example 5 adopts the same preparation method as Example 1, except that: the benzoxazine resin monomer powder and graphene are dried in a vacuum oven to remove moisture. At room temperature, 10% mass fraction of graphene of benzoxazine resin monomer and unground and screened resin monomer powder are weighed, added to a ball mill (vertical planetary ball mill XU-XQM-2A, Shanghai Xiniu Laber Instrument Co., Ltd.), and the grinding balls are put in. The ball-to-material ratio is 4:1, and the speed is set to 1500 rpm for ball milling for 1h. The composite material preform after ball milling is collected, added to the curing mold, and finally heated to open-ring polymerization to obtain the target product. The specific heating process of the temperature-raising ring-opening copolymerization is as follows: heat to 140°C for 1h, 160°C for 1h, 180°C for 1h, 200°C for 1h, and 220°C for 1h.

[0085] The mechanical properties of the composite material prepared in Comparative Example 5 did not change significantly, but the thermal conductivity and electrical conductivity were significantly reduced compared with those in Example 1, with a thermal conductivity of 0.52 W / mK and an electrical conductivity of 0.57 S / cm. In Example 1, the composite powder prepared by first grinding, sieving and then mixing has a good coating effect of graphene on the resin monomer powder, and the composite material prepared by this composite powder tends to form a dense, continuous thermal conductive network. However, during the process of ball milling the unground resin monomer with graphene and then curing, it is inevitable that the small-particle-size resin monomer powder produced during ball milling may be adsorbed between the graphene-coated resin particles, or mixed in the graphene layer coated on the outside of the large resin particles, affecting the coating effect. During curing, it melts and cuts off the thermal conductivity path, causing the thermal conductivity path to be short-circuited, blocking the transport of heat and electrons, and ultimately leading to a significant decrease in thermal and electrical conductivity.

Claims

1. A graphene-enhanced benzoxazine resin composite material, characterized in that: The benzoxazine monomer is ground into powder and mixed with graphene without adding other additives, and then heated and cured. The mass of the graphene is 8-15% of the mass of the benzoxazine monomer. The particle size of the benzoxazine monomer powder is 10-700 μm. The benzoxazine monomer is a bifunctional benzoxazine monomer, and its structure is shown in any one of the following: ; ; ; 。 2. The graphene-enhanced benzoxazine resin composite material according to claim 1, characterized in that: The particle size of the benzoxazine monomer powder is between 50 μm and 400 μm.

3. The graphene-enhanced benzoxazine resin composite material according to claim 1, characterized in that: The graphene is few-layer graphene.

4. A method for preparing the graphene-enhanced benzoxazine resin composite material according to claim 1, characterized in that: The steps include: (1) Grinding benzoxazine monomer into powder; (2) mixing benzoxazine monomer powder and graphene; (3) The mixed composite material powder is heated and solidified to obtain a composite material.

5. The method for preparing the graphene-enhanced benzoxazine resin composite material according to claim 4, characterized in that: The mass of the graphene in step (2) is 8-15% of the mass of the benzoxazine monomer.

6. The method for preparing the graphene-enhanced benzoxazine resin composite material according to claim 5, characterized in that: The mass of the graphene in step (2) is 10-12% of the mass of the benzoxazine monomer.

7. The method for preparing the graphene-enhanced benzoxazine resin composite material according to claim 4, characterized in that: The stirring speed in step (2) is 700-2500 rpm, and the stirring time is 10 min-2 h.

8. The method for preparing the graphene-enhanced benzoxazine resin composite material according to claim 4, characterized in that: The specific heating process of the heating and curing in step (3) is as follows: heat up to 140-150°C and keep warm for 1-2h, 160-170°C and keep warm for 1-2h, 180-190°C and keep warm for 1-2h, 200-210°C and keep warm for 1-2h, and 220-230°C and keep warm for 1-2h.

9. Use of the graphene-enhanced benzoxazine resin composite material according to claim 1 in electronic components and battery heat dissipation materials.

Citation Information

Patent Citations

  • In-situ intercalation powder preparation of graphene oxide-benzoxazine nano composite resin

    CN103012792A

  • Carboxylated graphene oxide benzoxazine nano-grade composite resin in-situ intercalated powder preparation method

    CN104151548A